A phase I/II study of intrathecal trastuzumab in human epidermal growth factor receptor 2-positive (HER2-positive) cancer with leptomeningeal metastases: Safety, efficacy, and cerebrospinal fluid pharmacokinetics. Issue 3 (10th August 2022) - Kumthekar, Priya U; Avram, Michael J; Lassman, Andrew B; Lin, Nancy U; Lee, Eudocia; Grimm, Sean A; Schwartz, Margaret; Bell Burdett, Kirsten L; Lukas, Rimas V; Dixit, Karan; Perron, Isabella; Zhang, Hui; et al.
Abstract: Background: Patients with human epidermal growth factor receptor 2-positive (HER2-positive) cancers have a high incidence of central nervous system (CNS) spread, but unfortunately systemic trastuzumab which targets the HER2 receptor has little CNS penetration. The purpose of this study was to determine the maximum-tolerated dose of intrathecal trastuzumab and its efficacy in patients with HER2-positive leptomeningeal disease (LMD). Methods: This multicenter study enrolled 34 LMD patients in a combined phase I/II study in treating patients with intrathecal trastuzumab. Any HER2-positive histology was allowed in the phase I; the phase II was limited to HER2-positive breast cancer. Results: Intrathecal trastuzumab was well-tolerated, with one dose limiting toxicity of grade 4 (arachnoiditis) occurring at the 80 mg twice weekly dose. The recommended phase II dose was 80 mg intrathecally twice weekly. Twenty-six patients at dose level 80 mg were included in evaluation for efficacy: partial response was seen in 5 (19.2%) patients, stable disease was observed in 13 (50.0%), and 8 (30.8%) of the patients had progressive disease. Median overall survival (OS) for phase II dose treated patients was 8.3 months (95% CI 5.2–19.6). The phase II HER2-positive breast cancer patients median OS was 10.5 months (95% CI 5.2–20.9). Pharmacokinetic (PK) studies were limited in the setting of concurrent systemic trastuzumab administration, however, did show stable cerebrospinal fluid (CSF) concentrations with repeated dosing suggest that trastuzumab does not accumulate in the CSF in toxic concentrations. Conclusion: This study suggests promise for potentially improved outcomes of HER-positive LMD patients when treated with intrathecal trastuzumab while remaining safe and well-tolerated for patients.